NEED FOR UPDATING OF REGULATORY REQUIREMENTS TO THE GREEN SYSTEM OF THE CITY OF SOFIA - Veselin Rangelov (World Science, 2022)
In recent years, the imperfection of the legislation in the field of spatial planning has become apparent, as can be seen especially in large cities and resorts. Sofia, as the capital of Bulgaria and the largest city in the country, has collected most of the negatives, and they are very clear about the development of the Green System of the city. This, together with advancing global climate change, calls for a new approach and the efficient use of green spaces to improve the city’s phytosanitary status.